Respostas
respondido por:
9
3x - 2y = 2 . (3)
5x + 6y = 8
9x - 6y = 6
5x + 6y = 8
14x = 14
x = 14/14
x = 1
3x - 2y = 2
3 . 1 - 2y = 2
3 - 2y = 2
- 2y = 2 - 3
- 2y = - 1 . (-1)
2y = 1
y = 1/2
S = { 1 ; 1/2 }
5x + 6y = 8
9x - 6y = 6
5x + 6y = 8
14x = 14
x = 14/14
x = 1
3x - 2y = 2
3 . 1 - 2y = 2
3 - 2y = 2
- 2y = 2 - 3
- 2y = - 1 . (-1)
2y = 1
y = 1/2
S = { 1 ; 1/2 }
respondido por:
5
Método da Adição:
3x - 2y = 2 (3)
5x + 6y = 8
9x - 6y = 6
5x + 6y = 8 (+)
14x = 14
x = 14/14
x = 1
5x + 6y = 8
5.1 + 6y = 8
5 + 6y = 8
6y = 8 - 5
6y = 3 (:3)
2y = 1
y = 1/2
R.: x = 1 e y = 1/2
3x - 2y = 2 (3)
5x + 6y = 8
9x - 6y = 6
5x + 6y = 8 (+)
14x = 14
x = 14/14
x = 1
5x + 6y = 8
5.1 + 6y = 8
5 + 6y = 8
6y = 8 - 5
6y = 3 (:3)
2y = 1
y = 1/2
R.: x = 1 e y = 1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás